Origin [videorecording (Blu-Ray)] - DuVernay, Ava; Ellis, Aunjanue; Bernthal, Jon; Yancy, Emily; Offerman, Nick, 1970-; Farmiga, Vera; McDonald, Audra; Nielsen, Connie, 1965-; Wittrock, Finn, 1984-; Underwood, Blair; Nash, Niecy; Wilkerson, Isabel (Decal Releasing, LLC, 2024)
While grappling with tremendous personal tragedy, Isabel sets herself on a path of global discovery. Despite the colossal scope of her project, she finds beauty and bravery while crafting one of the defining American books of our time.